Technologies for electrical power conversion, efficiency, and distribution methods and processes - Antchev, Mihail Hristov, 1955- (Engineering Science Reference, 2010)
"This book presents an overall description of electrical energy conversion technologies and required power electronic converters"--Provided by publisher.